Analysis of Factors Affecting Investment Decisions in The Housing Market - A Case Study of Housing Market in Vietnam - Nguyen, Luong Viet (2009)
There is still a gap in finding the other factors that might have some impact on investment decision in the housing sector. For that reason, this dissertation is aimed at making a contribution to establishing standardised criteria to identify and guarantee optimal real estate investment opportunities, especially in this market in Vietnam – the home country of the writer. It is the writer’s wish to make this dissertation a useful document for investors in their consideration and decisions, which would bring the utmost efficiency to the Vietnamese housing market. This is a practical action to show the writer’s gratitude to his home country and also to the United Kingdom, which has offered him priceless knowledge and research methodologies throughout the last seven years. It allows him to apply this knowledge scientifically and logically to compare markets in general and to study the Vietnamese market in particular. Importantly, practical contributions are thus made to the investment markets in both countries, making it the premise for mutual diplomatic, economic, cultural and social relationships.